Little man in W. Faulkner's creation - Pavilionienė, Aušrinė (Literatūra, 1974)
Man in the hostile capitalist world, man in a conflict with himself - these are the centrai problems of W. Faulkner's creation. With a view of revealing the main qualities of Faulkner's man (his refusal to put up with circumstances of life, an attempt to protect his dignity, his struggle for justice), the author of the paper analyses the images of representatives of the people.An unfortunate farmer (the Bundrens - "As I Lay Dying"), a farm labourer (Wash Jones - "Absalom! Absalom!"), a landless leaseholder (Mink Snopes - "The Hamlet", "The Town", "The Mansion"), being in a close contact with the earth, do preserve their live human nature. Primitively, yet naturally, they resist the crushing moral effects of the capitalist system - dehumanization and alienation.In this world, Faulkner's man attempts to perceive his self and the value of his own existence (Addie Bundren, Darl Bundren), he protests unconsciously against the humiliation of his dignity (Wash Jones), and goes a long way of developing his consciousness (Mink Snopes).Faulkner's little man is an embodiment of uncrushable pride, stoicism, obstinacy, and fury. These qualities are his only shield to protect him from blows of the cruel reality.
Keywords: -